ANALISIS KEPENTINGAN DAN KINERJA ATRIBUT PELAYANAN PADA WARUNG MAKAN IBU IIS DI BANDAR LAMPUNG - Alfina Ulfami; Wuryaningsih Dwi Sayekti; Rabiatul Adawiyah (Lampung University, 2026)
Warung Makan Ibu Iis is the target of this research, which seeks to examine critical features, performance attributes, and maintenance and improvement needs. A survey approach utilized to gather data from the research location. This research employed quota and non-probability sampling methods to compile a sample size of 64 individuals. The data collection was conducted in November 2023. To analyze the data, this research used Importance Performance Analysis (IPA). The findings of the research related to attribute performance of service at Warung Makan Bu Iis indicated that menu variety and parking availability were two areas that need some improvement. In addition, the feature that customers rank as having the lowest performance level was menu variety, with a score of 4.41, while the attribute that has the best ranks was the comfortableness of the venue, which rated about 4.56. Key words: Attributes, Importance, IPA, Performance, Warung Makan